Keterlibatan Perangkat Desa dalam Tata Kelola Perpustakaan Desa: Studi di Desa Sibuak, Kabupaten Kampar - Raja, Faisal Hamid Maka; Ayub, Daeng; Handoko, Tri; Arien, Wilasari; Jais, M. (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: This study aims to analyze community participation in the management of Sibuak Village Park, Tapung District, Kampar Regency, focusing on forms of community participation, factors influencing participation, the role of the village government, and challenges in park management. The study employed a qualitative approach with a case study design and was conducted over six months in 2026. Fourteen informants were selected purposively, consisting of the village head, village officials, park managers, community leaders, and local park users. Data were collected through observation, semi-structured interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing and verification. Data credibility was strengthened through source, technique, and time triangulation. The findings indicate that community participation was manifested through collective community service activities (gotong royong), park cleanliness maintenance, utilization of the park as a social interaction space, and involvement in village activities. Participation tended to be more evident when the village government communicated information openly and directly involved community members in activities. Factors influencing participation included community awareness, communication, village leadership, time availability, and perceived benefits. The village government functioned as a facilitator, motivator, and coordinator, while the main challenges included budget limitations, suboptimal coordination, and the absence of a sustainable management mechanism. These findings indicate that sustainable village park management requires an integrated contribution from the village government, community participation, effective communication, and coordination among stakeholders. Abstrak: Penelitian ini bertujuan untuk menganalisis partisipasi masyarakat dalam pengelolaan Taman Desa Sibuak, Kecamatan Tapung, Kabupaten Kampar, yang meliputi bentuk partisipasi masyarakat, faktor yang memengaruhi partisipasi, peran pemerintah desa, serta kendala dalam pengelolaan taman. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Penelitian dilaksanakan selama enam bulan pada tahun 2026. Informan dipilih secara purposive sampling dan berjumlah 14 orang, yang terdiri atas kepala desa, perangkat desa, pengelola taman, tokoh masyarakat, serta masyarakat pengguna taman. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña melalui kondensasi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Keabsahan data diperkuat melalui triangulasi sumber, teknik, dan waktu. Hasil penelitian menunjukkan bahwa partisipasi masyarakat diwujudkan melalui kegiatan gotong royong, pemeliharaan kebersihan, pemanfaatan taman sebagai ruang interaksi sosial, serta keterlibatan dalam kegiatan desa. Partisipasi cenderung lebih terlihat ketika pemerintah desa menyampaikan informasi secara terbuka dan melibatkan masyarakat secara langsung dalam kegiatan. Faktor yang memengaruhi partisipasi meliputi kesadaran masyarakat, komunikasi, kepemimpinan pemerintah desa, ketersediaan waktu, dan manfaat yang dirasakan. Pemerintah desa berperan sebagai fasilitator, motivator, dan koordinator, sedangkan kendala utama meliputi keterbatasan anggaran, koordinasi yang belum optimal, dan belum adanya mekanisme pengelolaan berkelanjutan. Temuan ini menunjukkan bahwa keberlanjutan pengelolaan taman desa memerlukan keterpaduan antara peran pemerintah desa, partisipasi masyarakat, komunikasi, dan koordinasi antarpemangku kepentingan.